The analysis of relaxation parameters changing during their measurement - N. N. Komova; A. D. Gruskov; G. E. Zaikov (Тонкие химические технологии, 2011)
It is shown that at research of such relaxation characteristics as the tangent of angle of mechanical losses, dissipation of mechanical energy as a result of the internal friction measured at periodic action of monoaxial pressure of compression on the sample of a polymer (LDPE) in the high-elasticity state, development of relaxation processes occurs in the sample. In this connection it is necessary to consider the temperature-time conditions of the experiment.